Comparative study on energy absorption capacities of normal and rubberized concrete columns under sinusoidal wave - Cho Zin Win; Khin Su Su Htwe; Nyan Myint Kyaw (Researcher and Lecturer Society, 2025)
This research explores the use of rubberized concrete composite as an innovative structural material designed to improve energy dissipation and enhance seismic resistance by incorporating recycled rubber crumb into concrete. A reference test model was constructed using normal concrete, while the remaining models were made from concrete in which a portion of the fine aggregates was partially replaced with crumb rubber particles. Lumped mass columns were tested on a shaking table using sine wave excitation to evaluate dynamic behaviour and seismic response with 4 Hz sinusoidal base motion. Acceleration measurements were obtained and analysed in MATLAB using Fast Fourier Transform (FFT), allowing for comparison between normal and rubberized concrete specimens. The results indicated that as the rubber content in the concrete increased, the frequency of the columns decreased under base excitation. Additionally, three-dimensional finite element simulations of lumped mass column models were conducted in ANSYS. Linear dynamic analysis was conducted to assess the system’s behaviour when subjected to harmonic loading. In addition, resonance conditions were also considered to assess the dynamic interaction of the column. With higher rubber content, the acceleration response is reduced due to the enhanced damping and energy absorption capabilities of rubberized concrete, leading to a significant decrease in peak acceleration values.